PATHWAY-2 and -3 - Zarifyan, Alla (MD Conference Express, 2015)
PATHWAY-2 and PATHWAY-3 demonstrated that potassium-sparing diuretics are safe and effective for the treatment of hypertension. Spironolactone was significantly more effective in controlling resistant hypertension than doxazosin or bisoprolol, whereas the amiloride/HCTZ combination neutralized the undesirable changes in blood glucose and potassium while significantly lowering blood pressure.